Integrated piezo-tribo hybrid acoustic-driven nanogenerator based on porous MWCNTs/PVDF-TrFE aerogel bulk with embedded PDMS tympanum structure for broadband sound energy harvesting. (15th June 2022) - Yu, Zhaohan; Zhang, Yongkang; Wang, Yunming; Zheng, Jiaqi; Fu, Yue; Chen, Dan; Wang, Guosheng; Cui, Jingqiang; Yu, Shengrui; Zheng, Li; Zhou, Huamin; Li, Dequn
Abstract: In this work, a novel type of acoustic-driven nanogenerator (ANG) that integrates piezoelectric and triboelectric effects is reported for broadband sound energy harvesting. With an internal structure combining beam-like porous multi-walled carbon nanotubes/polyvinylidene ﬂuoride-triﬂuoroethylene (MWCNTs/PVDF-TrFE) aerogel and polydimethylsiloxane (PDMS) tympanum, the integrated MWCNTs/PVDF-TrFE/PDMS (MCPP) ANG achieves efficient collection of acoustic energy through the enhanced vibration and friction generated internally. Besides, by eliminating the need for a contact separation structure or an external resonator cavity, this design greatly simplifies the structure and contributes to the flexibility and durability of the device. The MCPP ANG, with 20 wt% sodium carboxymethyl cellulose (SCMC), 2 wt% MWCNTs and 5% w/v PDMS, reaches an optimal output of 34.4 V and 1.74 μA under 150 Hz and 115 dB sound stimulation, corresponding to an areal power density of 11.62 mW/m 2 . It possesses a broad working bandwidth from 110 Hz to 400 Hz, and can directly illuminate 7 light-emitting diodes (LEDs) in series. Employing a novel, simple and effective structural design, the ANG proposed here achieves flexible and stable acoustic collection, offering a promising path toward sound spectrum analysis, noise detection and power supply for various low-power sensors. Graphical Abstract: A novel type of piezo-tribo hybrid acoustic-driven nanogenerator (ANG), with an internal structure combining beam-like porous MWCNTs/PVDF-TrFE aerogel and PDMS tympanum, is proposed for broadband sound energy harvesting. The ANG possesses a broad working bandwidth from 110 Hz to 400 Hz, and can directly illuminate 7 LEDs in series. ga1 Highlights: A piezo-tribo MCPP ANG based on porous aerogel bulk is proposed for sound capture. PDMS valve simplifies the structure and contributes to flexibility and durability. An appropriate amount of MWCNTs is doped to improve the charge transfer efficiency. The MCPP ANG possesses a broad working bandwidth from 110 Hz to 400 Hz. A self-powered acoustic sensor with music recognition capabilities is demonstrated.